Increased Virulence of Outer Membrane Porin Mutants of Mycobacterium abscessus - de Moura, Vinicius C. N.; Verma, Deepshikha; Everall, Isobel; Brown, Karen P.; Belardinelli, Juan M.; Shanley, Crystal; Stapleton, Megan; Parkhill, Julian; Floto, R. Andres; Ordway, Diane J.; Jackson, Mary (Frontiers in Microbiology, 2021)
Chronic pulmonary infections caused by non-tuberculous mycobacteria of the Mycobacterium abscessus complex (MABSC) are emerging as a global health problem and pose a threat to susceptible individuals with structural lung disease such as cystic fibrosis. The molecular mechanisms underlying the pathogenicity and intrinsic resistance of MABSC to antibiotics remain largely unknown. The involvement of Msp-type porins in the virulence and biocide resistance of some rapidly growing non-tuberculous mycobacteria and the finding of deletions and rearrangements in the porin genes of serially collected MABSC isolates from cystic fibrosis patients prompted us to investigate the contribution of these major surface proteins to MABSC infection. Inactivation of the each of the two Msp-type porin genes of M. abscessus subsp. massiliense CIP108297, mmpA and mmpB, led to a marked increase in the virulence and pathogenicity of both mutants in murine macrophages and infected mice. Neither of the mutants were found to be significantly more resistant to antibiotics. These results suggest that adaptation to the host environment rather than antibiotic pressure is the key driver of the emergence of porin mutants during infection.